Stable Histone Methylation Changes at Proteoglycan Network Genes Following Ethanol Exposure - Gavin, David P.; Hashimoto, Joel G.; Lazar, Nathan H.; Carbone, Lucia; Crabbe, John C.; Guizzetti, Marina (Frontiers in Genetics, 2018)
Alcohol use disorder (AUD) is a chronic mental illness in which patients often achieve protracted periods of abstinence prior to relapse. Epigenetic mechanisms may provide an explanation for the persisting gene expression changes that can be observed even after long periods of abstinence and may contribute to relapse. In this study we examined two histone modifications, histone 3 lysine 4 tri-methylation (H3K4me3) and histone 3 lysine 27 tri-methylation (H3K27me3), in the prefrontal cortex of Withdrawal Seizure Resistant (WSR) mice 21 days after 72 hours of ethanol vapor exposure. These histone modifications were selected because they are associated with active promoters (H3K4me3) and repressed gene expression in a euchromatic environment (H3K27me3). We performed a genome-wide analysis to identify differences in H3K4me3 and H3K27me3 levels in post-ethanol exposure vs. control mice by ChIP-seq. We detected a global reduction in H3K4me3 peaks and increase in H3K27me3 peaks in post-ethanol exposure mice compared to controls, these changes are consistent with persistent reductions in gene expression. Pathway analysis of genes displaying changes in H3K4me3 and H3K27me3 revealed enrichment for genes involved in proteoglycan and calcium signaling pathways, respectively. Microarray analysis of 7,683 genes and qPCR analysis identified 8 genes displaying concordant regulation of gene expression and H3K4me3/H3K27me3. We also compared changes in H3K4me3 and/or H3K27me3 from our study with changes in gene expression in response to ethanol from published literature and we found that the expression of 52% of the genes with altered H3K4me3 binding and 40% of genes with H3K27me3 differences are altered by ethanol exposure. The chromatin changes associated with the 21-day post-exposure period suggest that this period is a unique state in the addiction cycle that differs from ethanol intoxication and acute withdrawal. These results provide insights into the enduring effects of ethanol on proteoglycan and calcium signaling genes in the brain.